Use of Communication Pattern in State Agricultural University Students about Jobs - Shesh Narain Singh1, R. K. Doharey2, S. P. Sonkar, Manoj Kumar, G.S. Verma, M.P. Gautam, Mayur Gautam and Shrestha Gautam (Indian Journal of Extension Education, 2023)
This study was conducted in 4 main agricultural universities in Uttar Pradesh by interviewing 300 respondentswho were selected through proportionate random sampling technique on the criteria of having four yeardegree programme of B.Sc.(Ag.), two year degree programme M.Sc.(Ag.) and three year programmePh.D.(Ag.). The study depicted that the most use of communication media of respondents with mobilephone. An over whelming majority of the respondents were found using cellular phone as their main sourceof communication. The maximum number of respondents (62%) was observed in medium (3 to 7 hours)category of communication technology use in day, 35 per cent satisfied, familiarity with communicationtechnologies was television and most usefulness of communication technologies in career preferences wasmobile phone. The majority Purpose in use of communication Technology was computer information retrievalor data updating.